EFL READING IN THE LESSONS AT SPECIALIZED SCHOOLS IN UZBEKISTAN - Azamat Mukhriddinovich Kodirov, (Research Focus International Scientific Journal, 2025)
In this article, reading is discussed as an important part of learning a foreign language. The paper also covers key research concepts such as methods for developing reading skills in specialized schools, bottom-up and top-down reading strategies, schema theory and background knowledge, the impact of emotions and cultural context, and broad reading effectiveness.